2017
DOI: 10.1161/str.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Stroke in Patients With Silent Cerebrovascular Disease: A Scientific Statement for Healthcare Professionals From the American Heart Association/American Stroke Association

Abstract: Abstract-Two decades of epidemiological research shows that silent cerebrovascular disease is common and is associated with future risk for stroke and dementia. It is the most common incidental finding on brain scans. To summarize evidence on the diagnosis and management of silent cerebrovascular disease to prevent stroke, the Stroke Council of the American Heart Association convened a writing committee to evaluate existing evidence, to discuss clinical considerations, and to offer suggestions for future resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
314
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(329 citation statements)
references
References 191 publications
(240 reference statements)
5
314
1
9
Order By: Relevance
“…(33) Therefore, identification of a silent brain infarction in a primary brain tumor patient might serve as an opportunity to prevent a disabling stroke through initiation of targeted stroke prevention therapies. (34)…”
Section: Discussionmentioning
confidence: 99%
“…(33) Therefore, identification of a silent brain infarction in a primary brain tumor patient might serve as an opportunity to prevent a disabling stroke through initiation of targeted stroke prevention therapies. (34)…”
Section: Discussionmentioning
confidence: 99%
“…Overall, data from both observational studies and RCT indicate that reducing blood pressure may directly reduce the incidence and progression of WMH (Smith et al 2017). For statin treatments, trials have provided conflicting evidence as to whether statin treatment reduces WMH progression (ten Dam et al 2005;Mok et al 2009;Xiong et al 2014;Smith et al 2017). In people with type 2 diabetes mellitus, glucoselowering therapy did not reduce WMH progression (Launer et al 2011), though the association between type 2 diabetes and WMH remains unclear -most studies have found no association or only a weak association between diabetes and WMH (Prins and Scheltens 2015).…”
Section: Role Of Exercise In Mitigating Sivcimentioning
confidence: 99%
“…In the PROGRESS MRI substudy of patients with symptomatic stroke, patients treated for high blood pressure were less likely to have new WMH at a mean 3-year follow-up (Dufouil et al 2005). Overall, data from both observational studies and RCT indicate that reducing blood pressure may directly reduce the incidence and progression of WMH (Smith et al 2017). For statin treatments, trials have provided conflicting evidence as to whether statin treatment reduces WMH progression (ten Dam et al 2005;Mok et al 2009;Xiong et al 2014;Smith et al 2017).…”
Section: Role Of Exercise In Mitigating Sivcimentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that for every clinically recognized stroke 5 silent strokes occur (Dempsey, et al 2010, Rocque, et al 2012). This results in approximately 11,000,000 silent strokes per year (Dempsey, et al 2010, Dempsey, et al 2017, Smith, et al 2000, Smith, et al 2017, Snowdon, et al). Silent strokes are often detected on brain imaging examinations and while individuals do not present with the classic stroke symptoms (numbness, muscle weakness, difficulty speaking, ocular changes), they may demonstrate cognitive decline, especially in their executive function (Dempsey, et al 2017, Jackson, et al 2016, Rocque, et al 2012).…”
Section: Introductionmentioning
confidence: 99%